2016
DOI: 10.1097/sap.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breast Implant Location on the Risk of Capsular Contraction

Abstract: Risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
1
19
1
1
Order By: Relevance
“…The disadvantages of the prepectorally placed implant may be an inferior cosmetic outcome due to thin tissue coverage and implant visibility as well as a higher risk of capsular contracture [4,9]. A meta-analysis from 2016 evaluating more than 17,000 implants found that the risk of significant capsular formation increased more than two-fold with subglandular placement of the implant compared to subpectoral in augmented women [28]. However, the risk of capsular contracture may be less when an acellular dermal matrix (ADM) or an AMM is used [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of the prepectorally placed implant may be an inferior cosmetic outcome due to thin tissue coverage and implant visibility as well as a higher risk of capsular contracture [4,9]. A meta-analysis from 2016 evaluating more than 17,000 implants found that the risk of significant capsular formation increased more than two-fold with subglandular placement of the implant compared to subpectoral in augmented women [28]. However, the risk of capsular contracture may be less when an acellular dermal matrix (ADM) or an AMM is used [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…11 Reoperation rates for primary breast augmentation surgery approach 20% and are even higher for secondary augmentation over a patient's lifetime-the highest rate of all aesthetic procedures. 7,14 ■ CAPSULAR CONTRACTURE Capsular contracture is the most common complication of breast augmentation, 25 typically presenting within the fi rst postoperative year, 26,27 and the risk increases over time. 28 It occurs with both silicone and saline breast implants.…”
Section: ■ Implant Longevity and Rupturementioning
confidence: 99%
“…20 The etiology is not well understood and is presumed to be multifactorial, with proposed mechanisms and factors that include bacterial contamination, surface texturing, the implant pocket selected, the incision type, drain placement, antibiotic use, and smoking. 25 A meta-analysis from 17,000 implants found that the risk of capsular contracture was signifi cantly higher when an implant was placed in a subglandular pocket than in a submuscular pocket, 22,26 and that although texturing decreased capsular contracture compared with smooth implants, the effect was modest when a textured or smooth implant was placed in a submuscular location. 28 With regard to incision location, studies have reported that the incidence of capsular contracture is highest with transaxillary and periareolar incisions, and lowest with inframammary incisions.…”
Section: Considerations In Incision Locationmentioning
confidence: 99%
“…A paradigm shift in modern breast reconstruction occurred in 2001 with the introduction of acellular dermal matrix (ADM) allowing a direct to implant breast reconstruction that has become a standard procedure and evolved further using various types of biological and synthetic meshes (1)(2)(3)(4). The increased practice of one stage direct to implant reconstruction has resulted in an increased focus on the unsightly breast animation deformity (BAD) that has been suggested to be proportional to the degree of muscle involvement (5).…”
Section: Introductionmentioning
confidence: 99%
“…This change however, gives a resurgence of potential problems such as thin tissue coverage allowing visible implant edges, secondary ptosis and possibly increased rates of capsular contracture. These are potential risks, which needs to be examined in future studies (5,6). The aim of this visualized surgery paper was to visualize and highlight the technical disparities between a sub-and prepectoral direct to implant breast reconstructive techniques applied at our institutions.…”
Section: Introductionmentioning
confidence: 99%